Multi crop high efficiency seed drill with solar hybrid seed metering: a step toward precision and sustainability - Sultan, Umair; Khan, Alamgir Akhtar; Husnain, Syed Nabeel; Zohaib, Muhammad; Hashim, Norhashila (Frontiers Research Foundation, 2023)
High crop production with limited energy resources is always the priority area of developing countries. Conventional agricultural experimenting and crop production methods are time-consuming, challenging, laborious, and energy intensive. Various developments and experimental studies have been carried out for advancement in agriculture technologies. This study is mainly focused on the design and development of a unique high-efficiency seed drill machine to increase the energy efficiency of agricultural experiments, and crop production and conserve the tillage, seed, fertilizer, and power requirement. This machine has a special seed dividing head and seed distributor triggered with a mechanical timer. The mechanical timer is responsible to deliver seed to the seed distributor as per fixed plotting intervals. The seed distribution unit distributes the seeds uniformly in all furrows as per the pre-decided seed rate aided with a centrifugal glider aided with a DC motor powered by a 30 W solar PV plate and backup battery. Moreover, the machine has 9 × 9 s-type spring tines for seed and fertilizer, which are mainly designed for better soil pulverization and aeration with significant in-field resource conservation as per conventional alternatives. The effective width is seven feet and adjustable rows with versatile seed rate options. Overall, the results from different field tests verified the uniform seed dispersal with improved germination rate. The analysis of power requirements compared to conventional machines results in the 40% less power requirement. Overall, the machine has customized unique features for experiments and energy-efficient precision agriculture to conserve input resources.